Pengaruh Kecepatan Layanan dan Keamanan Sistem Informasi terhadap Kepuasan yang Dimoderasi oleh Kepercayaan Mahasiswa UniversitasNegeri Padang pada Penggunanaan BRIZZI Trans Padang - Renti Jasia Putri; Rino Rino (Universitas Negeri Padang, 2023)
The purpose of this study was to determine the effect of service speed and information system security on satisfaction moderated by trust in Padang State University students in the use of BRIZZI Trans Padang. This type of research is causative quantitative. The population in this study were all Padang State University students who were active in the January-June 2021 semester from BP 2016-2020. The number of research samples was 100 people and was selected using the Proportional Random Sampling technique. The data used is the type of primary data obtained by distributing questionnaires to Padang State University students with predetermined criteria. The analytical method that the researcher uses is Moderated Regression Analysis (MRA) with the help of the SPSS 18 program. The results show that: First, there is a positive and significant influence between service Speed on Padang State University student satisfaction on the use of BRIZZI Trans Padang. Second, there is a positive and significant effect between information system security on the joy of Padang State University students on the use of BRIZZI Trans Padang. Third, trust does not strengthen the impact of service speed on Padang State University student satisfaction in using BRIZZI Trans Padang and. Fourth, security does not enhance the influence of information system security on the joy of Padang State University students in using BRIZZI Trans Padang